Targeting Bruton's tyrosine kinase with ibrutinib in B‐cell malignancies. Issue 5 (3rd April 2015) - Wang, Y; Zhang, LL; Champlin, RE; Wang, ML
<x xml:space="preserve">Abstract</x> The B‐cell receptor signaling pathway, which is critical to the development and maturation of normal B‐cells, is emerging as an attractive therapeutic target in B‐cell malignancies. Ibrutinib is a potent irreversible inhibitor of Bruton's tyrosine kinase (Btk), a key kinase important for signal transduction in the B‐cell receptor (BCR) pathway. In preclinical studies, ibrutinib potently bound to Btk, inhibited BCR signaling, and decreased tumor cell proliferation and survival in many B‐cell malignancy models. Excellent safety and efficacy data in clinical trials have led to US Food and Drug Administration (FDA) approval of ibrutinib for previously treated mantle cell lymphoma (MCL) and chronic lymphocytic leukemia (CLL), as well as CLL with 17p deletion. Ongoing clinical studies have also demonstrated great potency of ibrutinib in treating other types of non‐Hodgkin's lymphoma (NHL), including diffuse large B‐cell lymphoma (DLBCL), follicular lymphoma (FL), and Waldenström's macroglobulinemia (WM). Combination of ibrutinib with chemoimmunotherapy and other promising novel agents in B‐cell malignancy therapy has also been under clinical investigation.